Pesquisa de Chlamydophila psittaci em ranfastídeos cativos no Estado de São Paulo, Brasil - Raso, Tânia de Freitas; Ferreira, Vivian Lindmayer; Teixeira, Rodrigo Hidalgo Friciello; Pinto, Aramis Augusto [UNESP] (FapUNIFESP (SciELO), 2012)
Chlamydophila psittaci (C. psittaci) has been detected in 460 avian species, among them the most frequent are the Psittaciformes, Columbiformes, Anseriformes and raptors. In Brazil, the main avian species recognized as healthy carriers belong to the order Psittaciformes and Columbiformes, but very few studies have been done in other bird families. Reports of the occurrence of this disease in the clinical form are rare in the Ramphastids; consequently, they are not commonly evaluated for this agent. The present study reports the investigation of C. psittaci in 25 captive ramphastids from a zoological park in São Paulo State, Brazil. Swabs samples from the cloaca were submitted to semi-nested polymerase chain reaction (semi-nested PCR) for direct detection of the microorganism. Additionally, blood samples obtained from these birds were submitted to the Complement Fixation Test (CFT) for detection of antibodies anti-C. psittaci. The presence of C. psittaci was not detected in the cloacal swab samples tested by the PCR. Nevertheless, 16% (4/25) of the bird's sera were positive by the CFT. Among the species with positive results, there are the saffron toucanet (Pteroglossus bailloni) and blacknecked- aracari (Pteroglossus aracari), two species with no descriptions of the survey of C. psittaci published in the literature. Intermittent elimination of C. psittaci is a feature of chronically infected birds; however the absence of a positiveantigen sample did not guarantee that the bird is Chlamydophila-free. The serological results obtained show that the ramphastids tested were previously exposed to the pathogen and developed immune response, but showed no clinical signs of the disease and didn't eliminate regularly the organism in their feces in the moment of the sample collection.
Survey on Chlamydophila psittaci in captive ramphastids in São Paulo State, Brazil
Keywords: Aracaris; Chlamydiosis; Chlamydophila psittaci; Ramphastids; Toucans